Instrumentation, Testing, and Measurement of a Strain Gauge for Implementing a Robotic Joint Torque Sensor - Ari, Joel Layme; Aranibar, Dennis Barrios (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
Mobile robots face the challenge of managing movements induced by inertia, overexertion, and stress caused by their own movements. Given this, it is necessary to find a balance between sensitivity and rigidity to achieve an optimal response in precision-oriented control algorithms. Therefore, the need arises to test new sensor alternatives and electronic configurations for better compensation against involuntary movements. This research presents a study on the instrumentation, testing, and measurement of a strain gauge for its potential implementation in torque control of mobile robot joints. Two models of strain gauges are used, both the BX1203AA model and the BX120-50AA model, analyzing variations in voltage, the number of gauges in the Wheatstone bridge, temperature, and degrees of flexion, with the goal of evaluating the feasibility of implementing these types of sensors in mobile robot joints to improve their torque and movement control. Finally, tests will be carried out with the humanoid robot Poppy to analyze the preliminary results of the implementation. All of this is aimed at contributing to the development of more precise and safer robotic solutions, capable of interacting more efficiently with their environment and with humans.